2011
DOI: 10.1016/j.juro.2010.11.046
|View full text |Cite
|
Sign up to set email alerts
|

Cadaveric Analysis of Periprostatic Nerve Distribution: An Anatomical Basis for High Anterior Release During Radical Prostatectomy?

Abstract: Simple numerical nerve quantification may be insufficient to accurately describe the periprostatic neural distribution. Calculating nerve bundle cross-sectional area confirmed that most neural tissue is in the posterolateral region, although the proportion located anterior increases from base to apex. Thus, higher release of the periprostatic fascia may be indicated toward the apex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 20 publications
0
18
0
1
Order By: Relevance
“…, Clarebrough et al. and Lee et al. counted the extraprostatic nerves by digitisation and computerised planimetry, while Eichelberg et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Clarebrough et al. and Lee et al. counted the extraprostatic nerves by digitisation and computerised planimetry, while Eichelberg et al.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we manually counted the number of nerve fibres per high‐power field as a surrogate of nerve density and found significant correlation with the surgeon's grading of NS. The periprostatic cross‐sectional area has also been used to measure the amount of ECNVT . We measured the cross‐sectional area of ECNVT on the posterolateral aspect of the prostate and found that it correlated best with the amount of NS intended by the surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…At the apex, 60% of the nerves were located posterolaterally and 40% were located anterolaterally [32]. In another study, Clarebrough et al [33] showed that the overall proportion of the nerve surface increased at the anterolateral side of the prostate, from 6% at the base to 7.6% at the mid part and to 11.2% at the apex; especially at the apex nerve fibres were more predominant along the anterolateral side of the prostate. Walz et al [34] evaluated these studies as having conflicting results which can be explained by the “interindividual variability” of the anatomy and also by the difference in methodology of the nerve surface and the number of nerve fibers.…”
Section: Fascial Anatomy Of Prostatementioning
confidence: 99%
“…Additionally, they stressed the variability of periprostatic nerve distribution [45]. Clarebrough et al [46] reported a similar periprostatic nerve distribution pattern that showed that the most periprostatic neural tissue was located in the posterolateral region with a smaller proportion on the anterior surface of the prostate.…”
Section: History Of Nsrp and Technical Advances In Fascial Surgerymentioning
confidence: 99%